(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
The aim of this study is to produce polyetheretherketone/hydroxyapatite (PEEK/HA) biocomposite using a nano-mixer single screw extruder. The use of a special design compounding machine, nano-mixer single screw extruder as a processing route could probably induce PEEK/HA composite with uniform compounding. Thermal testing and characterization were conducted to obtain information concerning the effects of single screw on the thermal properties and compounding characteristic. From this study, TGA analysis showed a minimal loss of weight for allÂ composite samples up to 500oC and above this temperature, the decomposition occured for PEEK/HA composite. Significant change in crystallinity was observed from DSC study of this composite where the increase in HA content was proportional to the crystalline structure in the composite. Apart from that, XRD measurement showed that HA was successfully embodied into PEEK matrix as the peak of intensity increased proportionally with the increase in HA content. Â Â